DIET PROVISION FOR ZOO ANIMALS IN CAPTIVE CONDITIONS OF LAHORE ZOO, - PAKISTAN S. K. Sikander; Z. Ali; A. Nemat; S. Ahmad; Z. Hussain; K. Saleem; M. N. Khan (Journal of Animal and Plant Sciences, 2015)
Zoological parks are considered as places or institutions where animals (wild and exotic) are kept within enclosures, are bred and exhibited. Predominantly, zoos are the sites aiming for wildlife conservation, endangered species preservation, scientific research and educational activities, also for recreational purposes for which they are provided with enriched environment and food. The study conducted is based on the diet provided to the animals at Lahore Zoo and further comparison of the food standards with those of diet standards for South Asian zoos. For this purpose, the study included the consultations from books, literature available at websites of zoo present across South Asia, the records and diet charts of animals at South Asian as well as Lahore Zoo and personal observations. The personal observations included parameters like time, hygienic conditions, food dispersal and enrichment of provided diet. The results of the study showed that most of the diet provision met the South Asian standards. Though, there was a variation in diet of some animals but the caloric values were equalized by providing any alternate food. Owing to the observation made it was concluded that the timing, hygienic conditions and dispersal ways of diet were overall satisfactory, however feeding enrichment was least observed. A nutritionally balanced diet comprising of
Keywords: Lahore Zoo; diet provision; captive conditions; comparison with standards.